PENINGKATAN KETERAMPILAN MENULIS CERPEN DENGAN MENGGUNAKAN PEMBELAJARAN PROBLEM CENTERED LEARNING (PCL) PADA SISWA KELAS V SDN 2 BONTO-BONTO DESA PADANG LAMPE KECAMATAN MA’RANG KABUPATEN PANGKEP - Nita Qhuljannah; Ummu Khaltsum; Andi Paida (Nusantara Hasana Journal, 2022)
This study aims to improve the learning process and short story writing skills by using Problem Centered Learning (PCL) for class V sdn 2 Bonto-Bonto students, Padang Lampe Village, Ma'rang District. This type of research is class action research (Class Action Research) which consists of two cycles, each cycle carried out in two meetings. The research procedure includes planning, implementing actions, observing and reflecting. The subjects in this study were the fifth grade students of SDN 2 Bonto-Bonto, Padang Lampe Village, Ma'rang District, with 11 students. The results of the short story writing skills of the fifth grade students of SDN 2 Bonto-Bonto, Padang Lampe Village, Ma'rang District using Problem Centered Learning (PCL) have increased.